Hvorfor siger russerne 'og', når danskerne siger 'eller'? Dansk logik versus russisk logik - Elena Lorentzen (Globe, 2016)
In this paper, I propose a new approach to phrasal coordination in general and disjunction in particular based on Durst-Andersen’s cognitive-semiotic theory of linguistic supertypes, according to which Russian is a reality-oriented language with a third-person-oriented speaker and Danish is a hearer-oriented language with a second-person-oriented speaker. I claim that the use of conjunction and disjunction in these languages is determined by their essential properties as two different super- types, viz. by the ground-situational nature of linguistic structures in Russian, the grammar of which functions as a model of situations in reality, and by the ground-propositional nature of linguistic structures in Danish, the grammar of which functions as a signal to the hearer to find situations behind the speaker’s information.